Harry Potter book series - trivial or not? - Brigita Pavšič (Acta Neophilologica, 2006)
The article explores  the extcnt to which the features  of trivial literature appear in the Harry Potter series by J. K. Rowling.This is done in comparison with another popular children's series, The Famous Five by Enid Blyton, which was analysed  by Igor Saksida. The main focus of the analysis is on the schematic representation of plot, characters and the exotic nature of the setting and time of the stories.